Malignant Transformation of Endometriosis in the Ischioanal Fossa - Jordan S. Klebanoff; Shivani K. Shah; Mark G. Cadungog (Case Reports in Obstetrics and Gynecology)
We present the case of a 28-year-old nulliparous female with malignant transformation of an ectopic focus of endometriosis in the right ischioanal fossa. A 28-year-old nulliparous patient with a past medical history of polycystic ovarian syndrome (PCOS) was diagnosed with endometrioid adenocarcinoma in her right ischioanal fossa. Initially, patient presented to an emergency department and underwent a CT scan of the appendix to rule out appendicitis. A multiloculated cystic lesion adjacent to the right obturator internus muscle was found. She underwent surgical resection of the mass, which confirmed FIGO grade 2 endometrioid adenocarcinoma, followed by localized radiation therapy. Malignancy arising in endometriosis is rare, and the influence of PCOS on the rate of malignant transformation is not well established.